An Exploratory Factor Analysis of a Prison Rape Elimination Act Survey in a Women's Prison - Shippen, Margaret E. (The prison journal, 2022)
Even with the dramatic increase in the number of female inmates in state and federal correctional institutions in recent decades, the criminal justice system continues to develop policies based on empirical research from male inmate programming. A shift in focus toward gender-responsive programming is challenging corrections to address women's needs. This study's data are a result of a settlement agreement between the United States Department of Justice (USDOJ) and a state Department of Corrections (DOC) to explore female inmates’ perceptions of sexual and physical safety in the state's largest correctional faculty. The Prison Rape Elimination Act Survey Instrument (PSI) was designed with 15 categories and 76 questions, including demographic data, sexual and physical safety factors, and items related to programs. Results of the exploratory factor analysis (EFA) indicate that the instrument has four factors detecting 41% of the variance explained. Recommendations are to conduct a confirmatory factor analysis (CFA) to assure that the instrument is psychometrically sound and the factors are verified.